National Lampoon's vacation [videorecording (DVD)] - Chase, Chevy; D'Angelo, Beverly; Coca, Imogene; Quaid, Randy, 1950-; Candy, John; Brinkley, Christie; Hall, Anthony Michael; Barron, Dana, 1966-
A suburban Chicago family travels across the United States on a comic trek to an amusement park, and encounters a series of disasters along the way.